Valuation of intangible assets: An analysis of practical limitations with a primary focus on monetary valuation methods for intangible assets - Denise Dudda (2019)
Within the study of intangible assets various terms and definitions have emerged without reaching a consensus. Nevertheless, such assets are composed of components that can be categorised into human capital, relational capital and structural capital. They have become the strategic key to the future success of any business due to of structural changes and their importance continues to grow as a result of increasing competition. Valuation of intangible assets is essential for their adequate strategic alignment, communication and successful business transactions. To demonstrate the breadth of available valuation approaches to intangible assets, this paper presents twenty-one methods from three categories that are aimed at determining their monetary value. Because valuation in the context of intangible assets continues to pose a great difficulty, these methods are analysed in terms of their practical limitations. Although the methods are diverse and pursue different approaches, limitations with regard to their application can be condensed. It was found that the applicability of methods is situational. Therein the degree of detail required based on the underlying valuation motive plays an essential role. Unawareness as to which method corresponds to the purpose can lead to unsatisfactory results, as well as to misguided decisions. In addition various methods are of limited use for practical application for one of three reasons. These reasons are the requirement for unavailable or exhaustive amount of data as well as high implementation costs due to complexity and limited significance of determined results.
Keywords: Intangible assets; monetary valuation methods; market capitalisation methods; return on assets methods; direct intellectual capital methods